IMPLEMENTATION OF ACCOUNTABILITY BASED VILLAGE OWNED ENTERPRISE GOVERNANCE IN BUSTANUSSALAM VILLAGE GAYO LUES - Dahlianita, Dahlianita; Muhtarom, Muhtarom (FISIP Universitas Malikussaleh, 2024)
Cooperative, participative, emancipatory, transparent, responsible, and sustainable are the guiding principles of BUMKp management. The BUMKp management should adhere to these six guidelines. Accountability to the public is one measure of accountability practices. Examining the public accountability system put in place at BUMKp Bustanussalam, Blangkejeren District, Gayo Lues Regency in 2021 is the goal of this study. Researchers use Hopwood and Tomkins' Gran theory to analyze this issue. The data for this study was gathered at BUMKp Bustanussalam by observation, interviews, and recording using a qualitative approach method. Strong regulations, community involvement, and government assistance all attest to BUM Kampung Bustanussalam's very transparent and accountable BUMK management. However, it is not ideal because staff members still encounter challenges while creating financial reports, including tight budgets, scarce human resources, a lack of time, and outdated facilities and infrastructure. Subsequent studies examine BUMKp innovations to improve openness.Prinsip dalam mengelola BUMKp meliputi kooperatif, partisipatif, emansipatif, transaparan, akuntabel, dan sustainabel. Keenam prinsip ini telah seharusnya diimplementasikan dalam pengelolaan BUMKp. Salah satu indikator praktik akuntabilitas adalah pertanggungjawaban kepada publik. Tujuan penelitian ini adalah menganalisis akuntabilitas publik yang diterapkan di BUMKp Bustanussalam, Kecamatan Blangkejeren, Kabupaten Gayo Lues Tahun 2021. Peneliti menganalisis permasalahan tersebut menggunakan Gran teori dari Hopwood dan Tomkins. Penelitian ini menggunakan metode pendekatan kualitatif dengan teknik pengumpulan data observasi, wawancara, dan dokumentasi yang dilakukan di BUMKp Bustanussalam. BUM Kampung Bustanussalam dalam pengelolaan BUMKnya sudah cukup akuntabel dan transparan dibuktikan dengan adanya regulasi yang kuat, partisipasi masyarakat, dan dukungan dari pemerintah namun belum maksimal karena masih ada hambatan-hambatan yang dihadapi pegawai dalam penyusunan laporan keuangan seperti terbatasnya anggaran dan sumber daya manusia, waktu, dan sarana dan prasarana. Penelitian yang akan datang menganalisis inovasi dari BUMKp untuk meningkatkan transparansi.